Flexible and self-healing 3D MXene/reduced graphene oxide/polyurethane composites for high-performance electromagnetic interference shielding. (18th August 2022) - Li, Haiyang; Ru, Xuanhe; Song, Ying; Wang, Huanping; Yang, Chenhui; Gong, Lei; Liu, Zhenguo; Zhang, Qiuyu; Chen, Yanhui
Abstract: As the application environment of electromagnetic interference (EMI) shielding composites becomes increasingly complex and changeful, the polymer materials with excellent mechanical properties and EMI shielding effectiveness (EMI SE) are highly desired, in order to maintain the long-term operation of equipment. Herein, we report a series of flexible and self-healing EMI shielding composites, which are developed by first constructing a highly electrically conductive 3D porous Ti3 C2 T x MXene/reduced graphene oxide (rGO) hybrid aerogel (MRG) by the freeze-drying and chemical reduction methods, and subsequently introducing dynamic crosslinked polyurethane containing Diels–Alder bonds (PUDA) into MRG by the vacuum assisted impregnation method. The 3D MXene/rGO/PUDA (MRGP) composites show a high EMI SE of 39.1 dB at an ultra-low 0.46 vol% of MXene and 0.65 vol% of rGO loading in the range of X-band (8.2–12.4 GHz), and the EMI SE can recover to 34.1 dB after three times of severing/healing cycles, retaining 91.4% of the EMI SE of the initial sample. In addition, the EMI SE of thrice healed MRGP composite hardly changes after 5000 bending cycles. The flexible and self-healing EMI shielding PUDA composites in our work show great potential application for long-term protection of portable communication electronic equipment. Graphical abstract: Image 1